Public Managers, Media Influence, and Governance: Three Research Traditions Empirically Explored. (November 2016) - Klijn, Erik Hans; van Twist, Mark; van der Steen, Martijn; Jeffares, Stephen
Nowadays, media and media logic have become important and inherent elements in everyday practices of public administration and policy making. However, the logic of the media is often very different from, and conflicting with, the logic of political and administrative life. So the question of how public managers experience and deal with media attention is more relevant than ever. An analytical sketch of the literature on the relationship between public managers and media provides three main categories of literature (public relations, agenda, and mediatization tradition). These three categories are used to develop statements (so-called Q-sort statements) to capture the way public managers experience their relationship with the media. A group of managers involved in oversight then sorted these statements into order of preference. The research reveals three different groups of managers who show different attitudes to media attention and whom we have labeled as adaptors, great communicators, and fatalists.